Model Pendidikan Penguatan Karakter Bitau’ati (Studi Di Man 2 Cirebon Dan Man 1 Brebes) - Nur Antoni ET; Subur Subur (Holistik, 2022)
Character Building Education (PPK) was born with the background of many juvenile delinquency, moral degeneration, the entry of radicalism that endangers the Republic of Indonesia and the decline in the sense of nationality and noble character in adolescents. However, the results of implementing KDP have not looked significant. Therefore, researchers are trying to uncover why this can happen and then provide a solution by creating a KDP model which is expected to be the best way to solve this problem. The KDP model that we designed was BITAUATI (guiding, monitoring and managing). To analyze the research, first the researcher used documentation data from books, newspapers, the internet and sources. To design the KDP model, the researchers used the Grounded method. Meanwhile, to analyze how the implementation of conventional KDP so far, how to implement the KDP Bitau'ati model and the results of its implementation, the researchers used the R and D method. the heart of the students so that they happily put it into practice. Basic skills training makes them ready to face the academic world, the world of work, the world of entrepreneurship. The student's delinquency rate decreased sharply, the students became more orderly and disciplined, with their awareness of maintaining order, tidiness, cleanliness and beauty.